Development of a general theory of lean production of goods and services - Valery V. Glushchenko; Milcha Handayani Tammubua; Effendi Sadly (Rowter Journal, 2024)
the subject of the article is methodological aspects of the theory of lean production of goods and services; the object of the article is lean production of goods and services; the purpose of the article is the formation of methodological provisions of the scientific theory of lean production of goods and services (the theory of thrift); to achieve the goal, this article solves the following tasks: search and analysis of publications on the topic of lean production of services for confirmation of the relevance of the research presented in this article; definitions of the object, method, functions, roles, laws of the scientific theory of lean production of goods and services; the functions, roles of the philosophy of lean production of goods and services are described; the directions of development of the philosophy and methodology of lean production of goods and services are investigated; the scientific methods in this article are: historical and logical method, system analysis, expert assessments; the scientific novelty of the article is determined by the development of the methodology of lean production of goods and services, the study and description of the structural elements of the theory of lean production of goods and services (the theory of thrift) and its structural elements.